Analisis Pengaruh Kompetensi, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Badan Penanggulangan Bencana Daerah Kabupaten Alor - Yustrina Anita Mau Demang (Jurnal Ilmiah Wahana Pendidikan, 2023)
The performance of an agency is determined by the success the agency's employees perform. Good performance will a good for agencies also. Several factors can help to support employee performance. These are work environment, democratic leadership, work motivation, and work discipline. The purpose for the study is to determine the department's of Transportation in the Alor Regency's effected the work environment, democratic leadership, and work motivation. there were 48 people in this study. It techniques using interviews, questionnaires, and techniques on observation. The t test, F test, and coefficient of determination to analyze the data. The results show that: With statistical tests with the t test, motivation for work has an partial effect for employee performance test with a significant level of 5% which has a probability value of 0.000 <0.005 or 5%; Work discipline has a partial effect on employee performance with statistical tests through the t test with a significant level of 5% which has a probability value of 0.035 <0.005 or 5%; Democratic leadership has a partial effect on employee performance with statistical tests through the t test with a significant level of 5% which has a probability value of 0.036 > 0.005 or 5%; The work environment has a partial effect on employee performance by statistical tests through the t test with a significant level of 5% which has a probability value of 0.000 < 0.005 or 5%, work motivation, work discipline, democratic leadership and work environment simultaneously affect employee performance by a significant value of 0.000 <0.05 or 5%. The influence of work motivation, work discipline, democratic leadership and work environment variables on employee performance is 0.881 or 88.1%.